2013
DOI: 10.1371/journal.pone.0070466
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Myxobacteria from Saline-Alkaline Soils in Xinjiang, China

Abstract: Fifty-eight terrestrial and salt-tolerant myxobacteria were isolated from the saline-alkaline soils collected from Xinjiang, China. Based on the morphologies and the 16S rRNA gene sequences, these isolates were assigned into 6 genera, Myxococcus, Cystobacter, Corallococcus, Sorangium, Nannocystis and Polyangium. All the strains grew better with 1% NaCl than without NaCl. Some Myxococcus strains were able to grow at 2% NaCl concentration, suggesting that these strains may be particular type of terrestrial myxob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
5
28
0
Order By: Relevance
“…No growth occurred at 44 °C. This is in accordance to Zhang et al (2003) who reported that almost all Myxococcus and Corallococcus strains grew within a temperature range of 10-37°C. Strains K9-5 and V3-1 were sensitive to spectinomycin, chloramphenicol, fusidic acid, oxytetracyclin, thiostrepton, and trimethoprim, but were resistant to ampicillin, gentamycin, kanamycin, cephalosporin, hygromycin, polymycin, and bacitracin.…”
Section: Antimicrobial Potential Of Pure Strainssupporting
confidence: 93%
See 2 more Smart Citations
“…No growth occurred at 44 °C. This is in accordance to Zhang et al (2003) who reported that almost all Myxococcus and Corallococcus strains grew within a temperature range of 10-37°C. Strains K9-5 and V3-1 were sensitive to spectinomycin, chloramphenicol, fusidic acid, oxytetracyclin, thiostrepton, and trimethoprim, but were resistant to ampicillin, gentamycin, kanamycin, cephalosporin, hygromycin, polymycin, and bacitracin.…”
Section: Antimicrobial Potential Of Pure Strainssupporting
confidence: 93%
“…The majority of strains were identified as either Myxococcus or Corallococcus species. A similarly large representation of these two genera was also found by Zhang et al (2003). Classification of the myxobacteria isolates on the basis of morphological features is represented in Table 2.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…1. Myxobacteria taxonomy was earlier associated only with morphology, which is adequate in differentiating between genera [30]. Nowadays, the identification of myxobacteria up to the species level is commonly derived from 16S rRNA gene analysis.…”
Section: Characterization Of the Most Potent Myxococcus And Corallocomentioning
confidence: 99%
“…According to the explanation for this phenomenon by Reichenbach (19), they are not actually indigenous limnetic organisms, and should originally come from terrestrial surroundings, and are finally transported into water bodies. Surprisingly, myxobacteria have also found in some extreme conditions, such as acidic wetlands (21), saline-alkaline soils (22), the arid desert (23), and even hot springs (24). More unexpectedly, a few myxobacteria have sporadically isolated from marine habitats (25), and different from known terrestrial myxobacteria, particularly in the requirement of sodium chloride roughly equivalent to the salinity of seawater (26).…”
Section: Introductionmentioning
confidence: 99%